Repeat-associated phase variable genes in the complete genome sequence of Neisseria meningitidis strain MC58. - Saunders, N; Jeffries, A; Peden, J; Hood, D; Tettelin, H; Rappuoli, R; Moxon, E (2000)
Phase variation, mediated through variation in the length of simple sequence repeats, is recognized as an important mechanism for controlling the expression of factors involved in bacterial virulence. Phase variation is associated with most of the currently recognized virulence determinants of Neisseria meningitidis. Based upon the complete genome sequence of the N. meningitidis serogroup B strain MC58, we have identified tracts of potentially unstable simple sequence repeats and their potential functional significance determined on the basis of sequence context. Of the 65 potentially phase variable genes identified, only 13 were previously recognized. Comparison with the sequences from the other two pathogenic Neisseria sequencing projects shows differences in the length of the repeats in 36 of the 65 genes identified, including 25 of those not previously known to be phase variable. Six genes that did not have differences in the length of the repeat instead had polymorphisms such that the gene would not be expected to be phase variable in at least one of the other strains. A further 12 candidates did not have homologues in either of the other two genome sequences. The large proportion of these genes that are associated with frameshifts and with differences in repeat length between the neisserial genome sequences is further corroborative evidence that they are phase variable. The number of potentially phase variable genes is substantially greater than for any other species studied to date, and would allow N. meningitidis to generate a very large repertoire of phenotypes through expression of these genes in different combinations. Novel phase variable candidates identified in the strain MC58 genome sequence include a spectrum of genes encoding glycosyltransferases, toxin related products, and metabolic activities as well as several restriction/modification and bacteriocin-related genes and a number of open reading frames (ORFs) for which the function is currently unknown. This suggests that the potential role of phase variation in mediating bacterium-host interactions is much greater than has been appreciated to date. Analysis of the distribution of homopolymeric tract lengths indicates that this species has sequence-specific mutational biases that favour the instability of sequences associated with phase variation.